Strategic Management Planning of Soybean Store Hadijanto Trisno With The Purpose of Developing Business and Facing Competition - Tedjalaksana, Retta Margaretta; Aldianto, Leo (The Indonesian Journal of Business Administration, 2013)
Every development demand a change, include in business world.  Small businesses that are still using traditional management system face a challenge to maintaining the business continuity and facing competition in this modern era.  Soybean Store Hadijanto Trisno, a hereditary business is facing some issues in running the business, which are company doesn’t have functional division, lack of workers and transport during peak hours, and no database system. Those business issues are explored through internal and external factors. The external factor will be explored by using PEST analysis (Political Economic Social Technological) and Porter’s five forces model and internal factor will be explore by using Value Chain Analysis and functional area analysis such as organization structure , Marketing, Operations, Human Resources and Information Technology. All explorations will lead to implementation of strategic management. The recommended solutions for Soybean Store Hadijanto Trisno is to implement strategic management that adopted corporate growth strategy to improving their business, using cost focus business strategy to facing the competition, and implementing functional strategies to increasing performance and reach the efficiency.  Keywords: strategic management, business strategy, growth strategy.